061 Metabolic alteration in hypertrophic cardiomyopathy (METAL-HCM Study): randomised double blinded placebo controlled trial of perhexiline therapy in patient with hypertrophic cardiomyopathy. (22nd September 2015) - Abozguia, K; Elliott, P; McKenna, W; Phan, TT; Nallur-Shivu, G; Ahmed, I; Maher, AR; Ashrafian, H; Watkins, H; Frenneaux, MP
Abstract : Background: Patients with hypertrophic cardiomyopathy (HCM) exhibit myocardial energetic impairment, but a causative role for this energy deficiency in the pathogenesis of HCM remains unproven. We hypothesised that the metabolic modulator, perhexiline would ameliorate myocardial energy deficiency and thereby improve diastolic function and exercise capacity. Methods: Forty-six consecutive patients with symptomatic exercise limitation (peak oxygen consumption – peak VO2<75% of predicted) due to non-obstructive HCM (mean age 55±0.26 years old) were randomised to perhexiline (n=25) or placebo (n=21). Myocardial PCr/ATP ratio, an established marker of cardiac energetic status, as measured by 31P magnetic resonance spectroscopy, LV diastolic filling (heart rate normalised time to peak filling, nTTPF) at rest and during exercise using radionuclide ventriculography, peak VO2, symptoms, quality of life and serum metabolites were assessed at baseline and at the end of the study (4.6±1.8 months). (ClinicalTrials.gov identifier, NCT00500552 ). Results: Perhexiline improved myocardial PCr/ATP ratios (from 1.27±0.02 to 1.73±0.02; p=0.003) and normalised the abnormal prolongation of nTTPF between rest and exercise (δ nTTPF: +0.11±0.008 s vs −0.01±0.005; p=0.03). These changes were accompanied by improvement in peak VO2 (22.2±0.2 to 24.29±0.2 ml/kg/min; p=0.003) and symptoms (NYHA class by 0.8 units p<0.001) (all p-values ANCOVA). Conclusion: In symptomatic HCM, perhexiline, a modulator of substrate metabolism, ameliorates cardiac energetic impairment, corrects diastolic dysfunction and increases exercise capacity. This study supports the hypothesis that energy deficiency contributes to the pathogenesis and provides a rationale for further consideration of metabolic therapies in HCM.